Geographic distribution of the European hare (Lepus europaeus) in Brazil and new records of occurrence for the Cerrado and Atlantic Forest biomes - De Faria, Gabriel Messias Moura; Rosa, Clarissa Alves; Castro Correâ, Guilherme Leandro; Puertas, Fernando; Olarte Jiménez, Karem Manuelita; Perillo, Lucas Neves; Hufnagel, Ludmila; Leles, Bruno [UNESP]; De Paula, Rogério Cunha; Guimarães Rodrigues, Flávio Henrique; Passamani, Marcelo (De Gruyter, 2016)
The introduction of alien species is among the main causes of biodiversity loss. There are many documented cases of introduced mammals having severe impacts on the ecosystem. The European hare (Lepus europaeus), native to Europe and Asia, was introduced to southern Brazil in the 1950s and has since expanded its geographic distribution considerably. In this study, we present a review of the known distribution of the European hare in Brazil, add new records of occurrence that expand the species distribution into southeastern Brazil and estimate the species dispersal rate in Brazil. We compiled at total of 135 distinct localities of occurrence for the species in Brazil, including published records and the previously unknown localities presented here. These records indicate a dispersal rate of 45.35 km/year for the introduced species. Of these known localities, 15 are in protected areas. Because of its high potential for even greater geographic dispersal and potential impacts on native species through competition and disease transmission, we recommend further research to better assess the species status and the implementation of public policies and management controls, especially in protected areas.
Keywords: alien species; biological invasion; exotic fauna